Physical exercise speeds up motor timing - Sysoeva, Olga V.; Wittmann, Marc; Mierau, Andreas; Polikanova, Irina; Strüder, Heiko K.; Tonevitsky, Alexander (Frontiers in Psychology, 2013)
This study aimed to examine effect of physical exercise on motor timing: personal, maximum and ‘once per second’ tapping. The acute effect was examined by comparing the baseline tapping with that after acute exercise in 9 amateur athletes, 8 elite synchronous swimmers and 9 elite biathletes. Then the baseline tapping was compared among athletes of different sports and professional levels (15 elite biathletes, 27 elite cross-country skiers, 15 elite synchronous swimmers and 9 amateur wrestlers) with a control group (44 non-athletes) not involved in regular exercise to examine the sport-specific or long-term effects. Maximum and ‘once per second’ tapping speed increased after acute physical exercise and were also faster in elite athletes compared to controls during the baseline condition. However, personal tapping tempo was not affected by exercise. In addition, physical exercise had no effects on the variability of the intertap interval. The accuracy of ‘once per second’ tapping was highest in elite synchronous swimmers suggesting sport-specific adaptations also to play a role. It is concluded that acute physical exercise selectively speeds up motor timing but does not affect its variability and accuracy, and this speeding-up is suggested to transfer into a long-term effect in elite athletes.